2015
DOI: 10.1108/ijwbr-08-2014-0036
|View full text |Cite
|
Sign up to set email alerts
|

Variety seeking by wine consumers in the southern states of the US

Abstract: Purpose -The purpose of this study is to investigate variety-seeking behavior among US wine consumers to determine if there are differences in their personal characteristics, values and relationship with wine. Design/methodology/approach -The research design uses a quantitative research study using data from an online survey of 401 US wine consumers. The Schwartz Value Inventory and the VARSEEK scale are used as measurement instruments. Data are analyzed using descriptive statistics, cluster analysis, ANOVA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 53 publications
4
45
1
Order By: Relevance
“…In business literature recent examples of market segmentation in wine business can be traced, but they are especially applied to different areas: the wine tourist (Alebaki & Lakovidou, ; Molina, Gómez, González‐Díazc, & Águdea, ), the use of a price segmentation (Thach & Olsen, ), the investigation of variety‐seeking behaviors in wine consumers (Olsen, Atkin, Thach, & Cuellar, ), the application of particular instruments or scales (Johnson & Bastian, ; Ristic, Johnson, Meiselman, Hoekc, & Bastian, ), the analysis of the effects of social influence and perceived usefulness on wine purchasing (Bonn, Kim, Kang, & Cho, ), and so on. As concerns data collecting, many studies use surveys online, but rarely they use conversations in social media as a platform for the analysis of the wine consumer.…”
Section: Conclusion and Indications For Future Researchmentioning
confidence: 99%
“…In business literature recent examples of market segmentation in wine business can be traced, but they are especially applied to different areas: the wine tourist (Alebaki & Lakovidou, ; Molina, Gómez, González‐Díazc, & Águdea, ), the use of a price segmentation (Thach & Olsen, ), the investigation of variety‐seeking behaviors in wine consumers (Olsen, Atkin, Thach, & Cuellar, ), the application of particular instruments or scales (Johnson & Bastian, ; Ristic, Johnson, Meiselman, Hoekc, & Bastian, ), the analysis of the effects of social influence and perceived usefulness on wine purchasing (Bonn, Kim, Kang, & Cho, ), and so on. As concerns data collecting, many studies use surveys online, but rarely they use conversations in social media as a platform for the analysis of the wine consumer.…”
Section: Conclusion and Indications For Future Researchmentioning
confidence: 99%
“…The last seven decades, variety seeking behavior is in academic literature (Olsen et al 2015). The marketing researchers have studied this topic because of a large number of choices for consumers with many areas (Olsen et al 2015).…”
Section: Variety Seeking Tendency (Vst)mentioning
confidence: 99%
“…The marketing researchers have studied this topic because of a large number of choices for consumers with many areas (Olsen et al 2015). Variety seeking is "the tendency of individuals to seek diversity in their choices of services and goods" (Kahn 1995, 139).…”
Section: Variety Seeking Tendency (Vst)mentioning
confidence: 99%
“…In the case of apparel, variety seeking and product characteristics interact with each other, but do not conclusively explain why consumers switch brands (Michaelidou and Dibb, 2006). Olsen et al (2015) investigated variety-seeking behavior among US wine consumers. Their research found that there were significant differences between high variety-seeking consumers compared to moderate variety-seeking consumers and variety avoiders.…”
Section: Variety Seekingmentioning
confidence: 99%
“…And, while generalizability to the population is not possible, the wine consumer diversity of geographic coverage across states may help mitigate some limitations within the convenience sample (Pedhazur and Schmelkin, 1991). We analyzed two segments of our respondent's variety-seeking behavior, high and low, whereas other research has measured three segments (Olsen et al (2015); future research might investigate three segments. Van Tripj et al's (1996) results found understanding product characteristics helpful in mitigating brand switching by consumers.…”
Section: Wine Club Membersmentioning
confidence: 99%